In vivo mitochondrial ATP production is improved in older adult skeletal muscle after a single dose of elamipretide in a randomized trial. - Baback Roshanravan; Sophia Z Liu; Amir S Ali; Eric G Shankland; Chessa Goss; John K Amory; H Thomas Robertson; David J Marcinek; Kevin E Conley (PLoS ONE)
Background Loss of mitochondrial function contributes to fatigue, exercise intolerance and muscle weakness, and is a key factor in the disability that develops with age and a wide variety of chronic disorders. Here, we describe the impact of a first-in-class cardiolipin-binding compound that is targeted to mitochondria and improves oxidative phosphorylation capacity (Elamipretide, ELAM) in a randomized, double-blind, placebo-controlled clinical trial. Methods Non-invasive magnetic resonance and optical spectroscopy provided measures of mitochondrial capacity (ATPmax) with exercise and mitochondrial coupling (ATP supply per O2 uptake; P/O) at rest. The first dorsal interosseous (FDI) muscle was studied in 39 healthy older adult subjects (60 to 85 yrs of age; 46% female) who were enrolled based on the presence of poorly functioning mitochondria. We measured volitional fatigue resistance by force-time integral over repetitive muscle contractions. Results A single ELAM dose elevated mitochondrial energetic capacity in vivo relative to placebo (ΔATPmax; P = 0.055, %ΔATPmax; P = 0.045) immediately after a 2-hour infusion. No difference was found on day 7 after treatment, which is consistent with the half-life of ELAM in human blood. No significant changes were found in resting muscle mitochondrial coupling. Despite the increase in ATPmax there was no significant effect of treatment on fatigue resistance in the FDI. Conclusions These results highlight that ELAM rapidly and reversibly elevates mitochondrial capacity after a single dose. This response represents the first demonstration of a pharmacological intervention that can reverse mitochondrial dysfunction in vivo immediately after treatment in aging human muscle.